2022
DOI: 10.3390/nu14183762
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Complementary Food in Germany: A 2020 Market Survey

Abstract: As consumption of commercial complementary food (CCF) during infancy and toddlerhood is common, the aim of the present study was to describe the current (2020) German market of CCF products targeted at infants and toddlers with a special focus on ingredients, macronutrients, and the practice of nutrient fortification. Information on age declarations, ingredients, energy and nutrient contents, and nutrient fortification was obtained in a market survey by contacting the producers and searching manufacturers’ web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…Soft meals formed the largest fraction of products included in this study, with the most substantial differences observed in nutrient profiles between price levels. The energy density (55 kcal/100 g) observed in this study was similar to or lower than that observed in previous studies conducted in other countries (60-99 kcal/100 g) (8,11,12,14,20,47,48,52) . In addition, soft meals in Japan had similar protein content (2•2 g/100 g) to those in the UK (2•6-3•1 g/100 g) (8,20) , Germany (1•4 g/100 g) (14) and South-East Asian countries (1•9-3•2 g/100 g) (18) ; however, they had lower protein content than soft meals in Australia (2•2-4•4 g/100 g) (11,12,48) and Italy (1•8-6•0 g/100 g) (15) .…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Soft meals formed the largest fraction of products included in this study, with the most substantial differences observed in nutrient profiles between price levels. The energy density (55 kcal/100 g) observed in this study was similar to or lower than that observed in previous studies conducted in other countries (60-99 kcal/100 g) (8,11,12,14,20,47,48,52) . In addition, soft meals in Japan had similar protein content (2•2 g/100 g) to those in the UK (2•6-3•1 g/100 g) (8,20) , Germany (1•4 g/100 g) (14) and South-East Asian countries (1•9-3•2 g/100 g) (18) ; however, they had lower protein content than soft meals in Australia (2•2-4•4 g/100 g) (11,12,48) and Italy (1•8-6•0 g/100 g) (15) .…”
Section: Discussionsupporting
confidence: 82%
“…We found that 90% and 80% of low-priced soft meals contained carrots and onions as ingredients, respectively. The frequent use of carrots and less use of bitter vegetables were consistently reported in the previous studies in Germany (14) , the US (19) , and the UK (20) . The carrot use frequency in this study (90% of soft meals) was much higher than that in other studies from the US (19) (31.9%), and the UK (20) (19.4%).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations